2013
DOI: 10.1016/j.chiabu.2013.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Child maltreatment severity and adult trauma symptoms: Does perceived social support play a buffering role?

Abstract: Objectives The current study investigates the moderating effect of perceived social support on associations between child maltreatment severity and adult trauma symptoms. We extend the existing literature by examining the roles of severity of multiple maltreatment types (i.e., sexual, physical, and emotional abuse; physical and emotional neglect) and gender in this process. Methods The sample included 372 newlywed individuals recruited from marriage license records. Participants completed a number of self-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
98
0
11

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 161 publications
(120 citation statements)
references
References 35 publications
11
98
0
11
Order By: Relevance
“…Rather, similar to studies of positive social support (e.g., Evans et al, 2013), negative social support showed no effect on trauma symptoms at higher levels of abuse severity. Negative support's lack of effect in the presence of more severe multitype abuse may indicate that once child maltreatment experiences have reached a certain threshold, day-to-day negative support interactions with a spouse do not worsen the survivor's trauma symptoms.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Rather, similar to studies of positive social support (e.g., Evans et al, 2013), negative social support showed no effect on trauma symptoms at higher levels of abuse severity. Negative support's lack of effect in the presence of more severe multitype abuse may indicate that once child maltreatment experiences have reached a certain threshold, day-to-day negative support interactions with a spouse do not worsen the survivor's trauma symptoms.…”
Section: Discussionmentioning
confidence: 76%
“…Despite evidence suggesting that spousal support moderates associations between early violence exposure and long-term functioning, recent studies indicate that the buffering effects of positive support may be limited to cases in which individuals are exposed to less severe, less frequent, or fewer types of violence (Evans, Steel, & DiLillo, 2013;Folger & Wright, 2013). For example, Salazar, Keller, and Courtney (2011) found that self-reported positive social support buffered against depressive symptoms only among individuals reporting fewer types of child maltreatment.…”
Section: Social Supportmentioning
confidence: 99%
“…Evans et al . () found that an increased severity of several maltreatment types predicted greater trauma symptoms for both women and men. The degree of severity may be evaluated by the instruments used to identify childhood trauma (Bernstein et al, ).…”
Section: Discussionmentioning
confidence: 97%
“…For those with low levels of perceived social support, intervention efforts may be most effective if they focus on assisting individuals in identifying sources of support in the hopes that this will lead to strengthened perceptions of support. This may involve not only increasing skills in inviting support from others but also addressing symptoms often present as a result of exposure to traumatic experiences, such as avoidance, emotional numbing, and feelings of detachment (Evans, Steele, & DiLillo, 2013). A number of interventions have been identified as effective means of enhancing perceived and received social support (Spilsbury & Korbin, 2013; Steese et al, 2005).…”
Section: Discussionmentioning
confidence: 99%